Rose Harbor in bloom a novel - Macomber, Debbie (New York Ballantine Books, 2013)
In Cedar Cove three women -- innkeeper Jo Marie Rose, young Annie Newton, and high-powered businesswoman Mary Smith -- make peace with their pasts as they boldly welcome their futures.
Keywords: Hotelkeepers; Life change events; Domestic fiction